Program Peningkatan Kewirausahaan Melalui Media Digital Untuk Pondok Yatim Putri Human Initiative - Meutia Handayani; Devi Mulia Sari; Cut Yunina Eriva (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2021)
this community service is carried out as a form of responsibility of Aceh Polytechnic Higher Education academics for the surrounding social environment. The object of this community service is the Pondok Santri Putri Human Initiative which has carried out entrepreneurial activities. There are several obstacles faced by the students so far. These obstacles include their lack of understanding of technology, the absence of a brand (brand) for their products so that later it will be difficult to market and promote online, and their understanding who have not been able to promote products digitally. From the problems faced, this community service activity is carried out to be able to help the students. This community service is carried out by conducting workshops to train in making attractive and competitive brands in online sales, as well as training students to market their products digitally through social media. The results of this study are expected to increase the income of the students through the products they produce